THE INFLUENCE OF TRUST AND SECURITY IN THE USE OF ELECTRONIC PAYMENT SYSTEM IN MANADO - Tani, Frangky (Universitas Sam Ratulangi, 2015)
Electronic payment is the way to make in the process of buying and selling customers in real estate market or online market easier. Electronic payments give innovation to consumer with transaction overseas like online shopping. This study aims to determine the influence of trust and security in the use of electronic payment system. Where the independent variables are trust and security influence in using electronic payment system as the dependent variable. This research used quantitative method. The analytical method used was multiple linear regression analysis. The data used in this research is primary data obtain through the questionnaire. The population is this study was taken at mall and superstore in Manado. Samples are taken from 100 respondents using purposive sampling technique. The result found that security is the most influential to usage of electronic payment system, then trust. Indeed, security and trust has significant influence on usage of electronic payment system. In fact customers are scared that during the transactions hackers and Internet interlopers will steal their information. The service providers should improve the security system to prevent fraud. The service provider must build customers trust, avoid the misuse of technologies, protect customer’s privacy and maintain the companies’ reputation. So the effectiveness of security can be created. Keywords: trust, security, electronic payment system.